2021
DOI: 10.1002/dta.3113
|View full text |Cite
|
Sign up to set email alerts
|

Analytical characterization of “etonitazepyne,” a new pyrrolidinyl‐containing 2‐benzylbenzimidazole opioid sold online

Abstract: This paper reports on the identification and full chemical characterization of the substance colloquially called “etonitazepyne” or “N‐pyrrolidino etonitazene” (2‐(4‐ethoxybenzyl)‐5‐nitro‐1‐(2‐(pyrrolidin‐1‐yl)ethyl)‐1H‐benzo[d]imidazole), a potent NPS opioid of the 5‐nitrobenzimidazole class. Identification of etonitazepyne was performed, on a sample purchased during routine monitoring of the drug market, using GC‐MS, HRAM LC‐MS/MS, 1H NMR, and FTIR. The chromatographic data, together with the FTIR data, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…The assignment of 1 H and 13 C signals observed for 28 – 31 was confirmed by the use of 2D‐NMR experiments, including 1 H‐ 13 C HSQC, 1 H‐ 13 C HMBC, 1 H‐ 15 N HSQC, 1 H‐ 15 N HMBC, and 2D‐NOESY. Numerous reports document the unambiguous structural assignment of several recent NPS, 41–45 including SCRAs, 5,7,21,46,47 using NMR spectroscopy. The comparison of 1 H NMR spectral data obtained for azaindazoles 28 – 31 with data previously reported by Longworth et al 48 for the analogous indazole SCRA, MDMB‐PINACA 32 (Figure 4), indicated that both the signals corresponding to distal fragments of the n ‐pentyl “tail” and tert ‐butyl portion of the amino acid “head” group maintain comparable chemical shift values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assignment of 1 H and 13 C signals observed for 28 – 31 was confirmed by the use of 2D‐NMR experiments, including 1 H‐ 13 C HSQC, 1 H‐ 13 C HMBC, 1 H‐ 15 N HSQC, 1 H‐ 15 N HMBC, and 2D‐NOESY. Numerous reports document the unambiguous structural assignment of several recent NPS, 41–45 including SCRAs, 5,7,21,46,47 using NMR spectroscopy. The comparison of 1 H NMR spectral data obtained for azaindazoles 28 – 31 with data previously reported by Longworth et al 48 for the analogous indazole SCRA, MDMB‐PINACA 32 (Figure 4), indicated that both the signals corresponding to distal fragments of the n ‐pentyl “tail” and tert ‐butyl portion of the amino acid “head” group maintain comparable chemical shift values.…”
Section: Resultsmentioning
confidence: 99%
“…An overview of the NMR spectroscopic data pertaining to azaindazoles 28-31 is summarized in the Supporting Information (see H- 13 C HSQC, 1 H- 13 C HMBC, 1 H- 15 N HSQC, 1 H- 15 N HMBC, and 2D-NOESY. Numerous reports document the unambiguous structural assignment of several recent NPS, [41][42][43][44][45] including SCRAs, 5,7,21,46,47 using NMR spectroscopy. (Figure 10).…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Etonitazepipne 100 na na na na 7. Etonitazepyne Around 100 na Identified in a toxicology case in May 2021, USA [ 56 ] na LC–HRMS/MS [ 66 ] GC–MS [ 66 ] NMR [ 66 ] 8. Isotodesnitazene ~ 75 34.8 na na LC–QTOF-MS [ 51 ] GC–MS [ 51 ] 9.…”
Section: Benzimidazole Opioidsmentioning
confidence: 99%
“…The analytical procedures are also described in each reference of Table 4 [ 51 , 53 – 55 , 57 , 65 , 66 ]. The pretreatments of compound products or biological samples such as L–L extraction and SPE methods are usually described in the references.…”
Section: Benzimidazole Opioidsmentioning
confidence: 99%
“…Predominately, newly emerging NSO's are identified and characterized from intact samples seized by law enforcement agencies [17], obtained during online monitoring of drug markets [18], or provided by individuals presenting for medical care after experiencing adverse effects following consumption [19], using a range of analytical chemistry techniques including Fourier-transform infrared spectroscopy (FT-IR), gas chromatography-mass spectrometry (GC-MS), liquid chromatography (LC-MS) using electrospray ionization (ESI), LC-tandem mass spectrometry (MS/MS) and Nuclear magnetic resonance (NMR). The sensitivity of GC-MS and LC-MS and -MS/MS methods also facilitate the use of these techniques for trace residue analysis of the contents of discarded drug paraphernalia (DDP), such as used syringes, where materials may be present in only microgram to nanogram quantities [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%